A geostatistical approach to downscaling climate forecasts. (26th March 2013) - Schultz, Colin
Abstract : Though global general circulation models are the tool of choice for forecasting the effects of climate change, their spatial resolutions are too broad for the needs of regional planners. To provide locally relevant information, modelers typically employ one of two techniques: producing a new forecast using a regional dynamic model or statistically downscaling the projections of the larger model. As a subset of the statistical approach, Jha et al . propose a geostatistical technique to translate climate‐modeling results to a smaller spatial scale.